A study on demography, clinical characteristics, management practice and outcome of childhood immune thrombocytopenia (ITP) in Kelantan - Daud, Rozaidahanim (2013)
Childhood ITP is a hematological disorder with differs worldwide and has been a topic of debate. To evaluate the demographic, clinical characteristics, management practice and outcome of childhood ITP in Kelantan and explore the factors associated with development of chronic ITP. This study was conducted via retrospective record review in 2 major tertiary centres in Kelantan. It involved all newly diagnosed ITP cases aged 6 months to 18 years from January 2001 till September 2012 who met all the study criteria. There were 90 patients included in this study with the median age at diagnosis of 5.4 years old and equal gender distribution. A peak incidence of children with ITP was observed within 3 months after rainy season, from February to April. The lowest case recorded was from May to July, the driest months of the year. History of recent infectious illness was detected in 53.3% of cases. A total of 53.3% of cases presented with cutaneous bleeding manifestation while 46.7% had mucosa or mucocutaneous bleeding. No intracranial bleeding or death documented in the first 6 months of diagnosis. The median platelet count at diagnosis was 10 109/L with 50% of patient had giant platelets in FBP. BMA was performed in 12 patients. There were 85.6% (n=77) of patients who received active medical interventions either with specific agent, platelet transfusion or both while the remaining were managed expectantly during first 6 months of diagnosis. Active medical intervention did not affect the final outcome for these patients. Of these 90 patients, 66.7% were acute, 24.6% were chronic, and 8.9% were undetermined. Female gender and the presence of giant platelet in the FBP were shown to be associated with the development of chronic ITP. Generally, childhood ITP has a good clinical outcome and active medical intervention has not been shown to influence the final outcome of the disease. Female gender and presence of giant platelet are significant predictors towards chronic ITP.